Multi-objective optimization using grey relational analysis for wire EDM of aluminium matrix composites. (2023) - Udaya Prakash, J.; Sivaprakasam, P.; Jebarose Juliyana, S.; Ananth, S.; Sarala Rubi, C.; Divya Sadhana, A.
Abstract: The creation of novel materials with high mechanical qualities necessitates the use of advanced machining techniques. Non-conventional machining processes alter the entire manufacturing scenario. Non-conventional machining processes swiftly replace conventional machining processes for obtaining better surface quality and a higher material removal rate. Based on grey relational analysis, this work proposes an efficacious method for optimising wire EDM machining parameters of AMCs with varied performance characteristics. Stir casting was used to make AMCs (413/B4 Cp ) using B4 C of 3%, 6% and 9% by weight as reinforcement and 413 as the matrix material. In this study, performance features MRR and SR are taken into account while optimising input parameters. The experimented GRG is 0.772, while the anticipated value is 0.784. This method helped to improve the WEDM process.